Intramuscular Hemangiolipoma of Right Masseter - Mohamad, Adam; Yusuf, Suhaimi; Mohamad, Irfan (International Journal of Human and Health Sciences (IJHHS), 2018)
Hemangiolipoma originated in muscle is rarely reported especially in otorhinolaryngology field. The presentations include swelling with discoloration of the surrounding skin. Complete surgical excision is the suggested treatment in both type infiltrating and noninfiltrating angiolipoma. We describe a case of angiolipoma in a child whereby the diagnosis was suspected after magnetic resonance imaging with gadolinium. Keywords: Angiolipoma, Masseter Muscle, Magnetic Resonance Imaging. International Journal of Human and Health Sciences Vol. 01 No. 02 July’17. Page : 86-88